2018
DOI: 10.1007/s00299-018-2264-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CAT in the detoxification of HT-induced ROS burst in rice anther and its relation to pollen fertility

Abstract: HT-induced ROS burst in developing anther is closely related to the lowered CAT activity as the result of the markedly suppressed OsCATB transcript, thereby causing severe fertility injury for rice plants exposed to HT at meiosis stage. The reproductive stage of rice plants is highly sensitive to heat stress. In this paper, different rice cultivars were used to investigate the relationship of HT-induced floret sterility with reactive oxygen species (ROS) detoxification in rice anthers under well-controlled cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 38 publications
6
58
0
7
Order By: Relevance
“…These results demonstrated that nanoparticles were accumulated in root tip. These results were similar with in rice, as the previous reported (Du et al, 2018).…”
Section: Nanoparticles Caused Sodium Export From Wheat Seedling Plantsupporting
confidence: 93%
“…These results demonstrated that nanoparticles were accumulated in root tip. These results were similar with in rice, as the previous reported (Du et al, 2018).…”
Section: Nanoparticles Caused Sodium Export From Wheat Seedling Plantsupporting
confidence: 93%
“…Trxs usually work in a complex with several other proteins involved in ROS scavenging (Yoshida et al ., ; Zhang et al ., ). In addition to Trxs, antioxidant enzymes, predominantly superoxide dismutase (SOD) and catalase (CAT), also help to reduce cellular ROS levels in rice, particularly under high temperature stress, thus avoiding male sterility (Zhao et al ., ,). Several mutants defective in ROS homeostasis displayed developmental defects and sterility mainly due to ROS accumulation (Hu et al ., ; Heng et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested its role as a negative regulator of heat stress tolerance in rice and seems that its role as a negative regulator of abiotic stresses is conserved. Rice SOD and CAT are key stress responsive genes which regulate the level of SOD and CAT enzymes in rice (Zhao et al . 2018a; Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…2018b). Higher expression of these genes is linked with improved heat tolerance in rice (Zhao et al . 2018a; Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation